Secondary products of tomato processing in the technologies of food products - Benderska (Dushchak), Olga; Levkivska (Muzika), Tetiana (My University, 2021)
Department of Canning Technology, National University food technology developed a comprehensive processing technology tomato raw materials. A feature of the proposed technology is additional use for processing of secondary resources of tomato processing – tomato seeds and tomatoes of technical ripeness. Кафедрою розроблено комплексну технологію перероблення томатної сировини. Особливістю запропонованої технології є додаткове використання для переробки вторинних ресурсів томатопереобки – томатного насіння та томатів технічної стиглості.
Вторинні продукти перероблення томатів в технологіях харчових продуктів
Keywords: tomatoes; proteinases; seeds; inactivation; trypsin; томати; протеїнази; насіння; інактивація; трипсин; кафедра технології консервування